PENERAPAN OMNIBUS LAW DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN INDONESIA - Alfan Prahasta Adhisatya; . Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2023)
Indonesia has passed many government regimes. Regime change is a process of succession of powers in which each journey results in different policies. This also resulted in the establishment of many laws and regulations in accordance with the needs of each power holder, which is part of his policy as well. This then forms a disharmonic and hyper-regulated legal ecosystem. Therefore, a policy breakthrough was initiated in the process of establishing legislation, namely Omnibus Law. But the problem and must first be answered is the concept of Omnibus Law has not been regulated in the legislation. Law No. 15 of 2019 concerning Amendment to Law No. 12 of 2011 concerning the Establishment of Legislation so far has not been drafted with the aim of accommodating the existence of Omnibus Law. It is then able to describe the application of Omnibus Law in the Indonesian Legal System.